The Hijri Lunar and Solar Calendars: Differences, Historical Background, and Their Cultural and Scientific Significance (Zien Journal of Social Sciences and Humanities, 2025)
Throughout human history, various calendar systems have been developed to measure and regulate time. Among the most widely used are the Islamic calendar (Hijri calendar) and the Gregorian calendar. This article examines the principal differences between these two calendar systems and highlights the distinctive features and characteristics of each